Shakespeare : the art of the dramatist - Frye, Roland Mushat (Routledge library editions. Shakespeare, 2005)
This edition first published in 1982. Previous edition published in 1972 by Houghton Mifflin. Outlining methods and techniques for reading Shakespeare's plays, Roland Frye explores and develops a comprehensive understanding of Shakespeare's drama, focussing on the topics which must be kept in mind: the formative influence of the particular genre chosen for telling a story, the way in which the story is narrated and dramatized, the styles used to convey action, character and mood, and the manner in which Shakespeare has constructed his living characterizations. As well as covering.